Should all elective knee radiographs requested by general practitioners be performed weight-bearing? - Chen,A; Balogun-Lynch,J; Aggarwal,K; Dick,E; Gupte,CM (SpringerPlus, 2014)
The aims of this study were to: [1] Assess the number of patients with suspected knee osteoarthritis that underwent repeat weight-bearing(WB) knee radiographs in the orthopaedic clinic following initial non-WB radiograph requested by their general practitioner (GP). [2] Confirm whether repeating WB knee views changed radiology reports. [3] Determine the number of London trusts with protocols for routinely performing WB views. A Retrospective cohort study of 1968 patients aged >40 years referred to a London teaching hospital for knee radiographs over 12 months. Radiographs were identified as WB/non-WB. Subsequent repeat WB views performed in those that went on to have an orthopaedic consultation were also documented. A consultant musculoskeletal radiologist reported both images. A proforma containing a likert scale of severity for commonly reported abnormalities in knee osteoarthritis and criteria from the Kellgren and Lawrence scale was used for reporting. London NHS Trusts were surveyed to identify if protocols were in place for performing WB views. A total of 1,968 patients underwent knee radiographs, of which 1922 (97.7%) had initial non-WB radiographs. Of the 56 patients in this group that underwent required repeat WB radiographs, joint space narrowing was reported as more severe on WB versus non-WB radiographs (p = 0.035). Only 54% of departments routinely performed WB radiographs. Few patients (2.3%) referred by GPs have WB radiographs requested. Some of those referred for a specialist opinion required repeat WB views. Nearly half of London hospitals do not routinely perform WB radiographs. This represents a significant financial burden to the NHS, increased radiation exposure and wasted patient/clinician time. We propose that all GP requested knee radiographs be performed as WB unless otherwise stated.